Piezophotonic effect based on mechanoluminescent materials for advanced flexible optoelectronic applications. (January 2019) - Wang, Xiandi; Peng, Dengfeng; Huang, Bolong; Pan, Caofeng; Wang, Zhong Lin
Abstract: Recently, there has been an increasing research interest in the emerging fields of piezophotonics, which is the great interesting physics responsible for numbers of important technologies such as light source, smart sensor and mechanoelectronics. Piezophotonic effect is the coupling between the piezoelectric polarization and the photonic excitation in crystal that has a non-central symmetry. The strain-induced piezopotential can stimuli the photon emission without additional energy excitation such as light and electricity, which also offers great new opportunities of manipulating and fabrication of flexible optoelectronic devices. In this review, we will give a detailed description of the piezophotonic effect including its theoretical fundamental and practical applications. The piezophotonic light emission in doped ZnS CaZnOS, SrAl2 O4 and LiNbO3 attract great interesting during the past years, and researchers have executed many scientific inquiries into flexible/stretchable optoelectronic devices. Until now, significant breakthroughs have been achieved on piezophotonic e-signature system, visible wearable electronic devices and multi-physical coupling devices. Certainly, rapid innovations in this field will be quite significant to the future of human life. Graphical abstract: Piezophotonic effect is the coupling between the piezoelectricity and the photonic excitation. The strain-induced piezopotential can stimuli the photon emission without additional energy excitation such as light and electricity, which also offers great new opportunities of manipulating and fabrication of flexible optoelectronic devices. In this review, we will give a detailed description of the piezophotonic effect including its theoretical fundamental and practical applications.fx1 Highlights: Theoretical fundamental of the piezophotonic effect. The strain-induced piezopotential can stimuli the photon emission, which is the core content of the piezophotonic effect. The introduction of flexible/stretchable optoelectronic devices based on the piezophotonic effect. Significant breakthroughs have been achieved on piezophotonic e-signature system, visible wearable electronic devices and multi-physical coupling devices. Advances in piezophotonics materials and future novel trends for visual electronic skin.